2014
DOI: 10.1093/mnras/stu1466
|View full text |Cite
|
Sign up to set email alerts
|

Transonic galactic outflows in a dark matter halo with a central black hole and its application to the Sombrero galaxy

Abstract: We have classified possible transonic solutions of galactic outflows in the gravitational potential of the dark matter halo (DMH) and super massive black hole (SMBH) under the assumptions of isothermal, spherically symmetric and steady state. It is clarified that the gravity of SMBH adds a new branch of transonic solutions with the transonic point in very close proximity to the centre in addition to the outer transonic point generated by the gravity of DMH. Because these two transonic solutions have substantia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 68 publications
5
24
1
Order By: Relevance
“…Specifically, although the trace of the galactic outflow can be seen in X-ray observations, the gas density distribution in this galaxy is well reproduced as a hydrostatic state. Further, Igarashi et al (2014) have indicated that the hot gas of this galaxy may form a slowly accelerating transonic outflow. In the widely spread subsonic region, it is difficult to distinguish the gas density from a hydrostatic state.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Specifically, although the trace of the galactic outflow can be seen in X-ray observations, the gas density distribution in this galaxy is well reproduced as a hydrostatic state. Further, Igarashi et al (2014) have indicated that the hot gas of this galaxy may form a slowly accelerating transonic outflow. In the widely spread subsonic region, it is difficult to distinguish the gas density from a hydrostatic state.…”
Section: Introductionmentioning
confidence: 92%
“…2 and 4 of Tsuchiya et al 2013 or Fig. 1 of Igarashi et al 2014). In the type B solutions, it is plausible to consider that the outflow starts at the vicinity of the locus of the O-point (just below the O-point of type B in Fig.1).…”
Section: Transonic Solutions Incorporating Dmh Gravitational Potentialmentioning
confidence: 99%
See 3 more Smart Citations